PENGARUH MEDIA PLANETARY POP-UP TERHADAP PERKEMBANGAN KOGNITIF SISWA SMPN 14 BOGOR - Haniyah, Maisan; Rozak, Dewi Nur Lathifa Abdul; Nursamsu, Alisah; Sitanggang, Renata Kantate Getsemani; Istiqomah, Rika; Oktaviani, Maya (LPPM, Universitas Negeri Jakarta, 2023)
This research aims to explore the boundaries opened by using Planetary Pop-Up media and reveal the extent to which this media can enrich students' cognitive abilities. The focus is to deepen understanding of the solar system and the invaluable sun. The method used is Research and Development (R&D) with the ADDIE development approach which includes the stages of analysis, design, development, implementation, and evaluation. The population of this study included all grade 7 students at SMPN 14 Bogor, and the sample was selected randomly using the Simple Random Sampling (SRS) method to ensure fairness in selection. Data collection was carried out through media trials, interviews, pre-test, and post-test. Data analysis used the T-test technique, focusing on paired t-tests to reveal differences before and after using Planetary Pop-Up media. The results of the analysis show that the use of this media does not provide a significant difference in the average pre-test and post-test scores. It is hoped that these findings can significantly contribute to the development of effective learning media, especially in improving students' cognitive abilities. Apart from that, it is hoped that this research can also be a reference for other researchers interested in conducting similar research using a Piagetian theory-based approach. This discovery is a step towards miracles in the world of education, and it is hoped that it will inspire other daredevils to undertake similar adventures. In all the uniqueness and light found, the hope is that these findings will become a guide that guides knowledge seekers to the right path, creating untold miracles in the world of education.